Parish of Mugga, County of Bland - New South Wales. Department of Lands (Sydney : The Department, 1983)
Cadastral map showing parish boundaries and land holdings.
Also available online
Keywords: Real property -- New South Wales -- Mugga -- Maps; Mugga (N.S.W.) -- Maps